2020
DOI: 10.3389/fvets.2020.00570
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular Administration of Allogeneic Adipose Derived MSCs Reduces Pain and Lameness in Dogs With Hip Osteoarthritis: A Double Blinded, Randomized, Placebo Controlled Pilot Study

Abstract: This study was conducted to investigate the therapeutic effect of allogeneic adipose-derived MSCs on dogs with hip osteoarthritis (OA). Twenty dogs with bilateral osteoarthritis of the coxofemoral (hip) joint, diagnosed by a veterinarian through physical examination and radiographs were randomly allocated into four groups. Group 1 served as a placebo control and were injected with 0.9% sodium chloride (saline) (n = 4). Group 2 were injected with a single dose of 5 million MSCs (n = 5). Group 3 received a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…The use of MSC in canine medicine is also becoming more popular. Canine MSC have been used successfully in several in vivo studies, especially for the treatment of osteoarthritis [ 8 , 9 , 10 ], but also for various other conditions such as atopic dermatitis [ 11 , 12 ], diabetes mellitus [ 13 ], inflammatory bowel disease [ 14 ], or to support neuroregeneration following vertebral compression fractures [ 15 ]. At the same time, there is a need to improve and harmonize canine MSC production processes.…”
Section: Introductionmentioning
confidence: 99%
“…The use of MSC in canine medicine is also becoming more popular. Canine MSC have been used successfully in several in vivo studies, especially for the treatment of osteoarthritis [ 8 , 9 , 10 ], but also for various other conditions such as atopic dermatitis [ 11 , 12 ], diabetes mellitus [ 13 ], inflammatory bowel disease [ 14 ], or to support neuroregeneration following vertebral compression fractures [ 15 ]. At the same time, there is a need to improve and harmonize canine MSC production processes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies evaluating biosafety of allogeneic MSCs injections as an alternative to autologous injections have been published ( 4 8 ). Isolated and repeated injections of allogeneic MSCs in horses under several conditions ( 9 11 ) can generate positive results in different injuries and administration routes ( 12 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical application of MSC-based therapy in veterinary medicine comprises of multiple target diseases, with the vast majority being focused on musculoskeletal conditions such as osteoarthritis (8,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), cruciate ligament disease (9,(35)(36)(37)(38), hip dysplasia (39), bone fractures and lesions (40,41), muscle tears (42,43) and tendinopathies (44,45). Canine clinical studies have also shown promising results for the treatment of diseases of the gastro-intestinal tract (46)(47)(48), central nervous system (49)(50)(51)(52)(53), cardiovascular system (54,55), cutaneous (56)(57)(58)(59) and ocular conditions (60)(61)(62)(63), resulting in encouraging safety and efficacy data (Figure 2).…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…In canine OA clinical studies, the characterization of MSCs immunophenotype is most often regarded as a routine protocol based on a minimal standardized conventional set of set of positive (CD44, CD29, CD90) and negative surface markers (CD34, CD45, MHC-II) (8,9,29,31,34). From this practical perspective, immunophenotyping is used to demonstrate the surface identity of the cells manufactured in different facilities worldwide, which however does not correlate with the functionality and therapeutic efficacy of the final product.…”
Section: Cell Characterizationmentioning
confidence: 99%